Aspects of Analysis of the Assets of Building Companies in Bulgaria for the Period 2012 – 2015 - Ignatova, Nikolinka (Research Papers, 2018)
The report analyzes and compares the indicators that characterize the status and dynamics of assets in construction companies. The object of the survey is the construction companies Vodstroy 98 AD and Trace Group Hold AD. Subject of the survey are the following indicators: provision of non-current and current assets, their composition and structure, the use and effectiveness of non-current and current assets. Subject of analysis are the indicators for utilization of non-current tangible assets, effectiveness determined on the basis of non-current and current tangible assets, turnover and circular turnover of inventories; efficiency and cost-effectiveness of asset use, and others. The aim is to reveal the strengths and weaknesses in asset management and to outline the means for their improvement. Applied are the comparative method, the index method, the growth method, the correlation and regression analysis, etc. The study covers the period from 2012 to 2015.
Keywords: Non-current and current assets; Efficiency and construction companies; Profitability